Fuzzy bicompletable quasi-fuzzy distance space - Kider, Jehad; J. Hassan, Aisha (International Journal of Applied Mathematical Research, 2016)
In this paper we introduce the definition of quasi-fuzzy distance space then we discuss several properties of this space after we give an example to illustrate this notion. Then we show that the existence of a quasi-fuzzy distance space which is not fuzzy bicompletable. Here we prove that every fuzzy bicompletable quasi-fuzzy distance space admits a unique [up to fuzzy isodistance] fuzzy a bicompletion.